STRENGTH CHARACTERISATION AND CLASSIFICATION OF COMBINED GLULAM BEAM MADE FROM OPEPE (Nauclea diderrichii) AND OBECHE (Triplochiton scleroxylon) TIMBERS (FUDMA JOURNAL OF SCIENCES, 2023)
Quality timber species are declining due to over-exploitation in Nigeria. This has propelled the utilisation of low-grade timbers species that are considered for low-end constructions in the past which called for concern. This study establishes the viability of a typical beam made from locally sourced non-durable Obeche (Triplochiton scleroxylon) with highly durable Opepe (Nauclea diderrichii) timber specie in a combined glulam form, using polyvinyl acetate (PVA) adhesive which serves the impact of environmental sustainability and reduced cost of engineering construction. Seasoned timber samples and PVA adhesive were all obtained locally in Nigeria. Beam specimens were tested in the Department of Civil Engineering, Ahmadu Bello University, Zaria according to EN 338 (2009). Based on tests, it is evident that solid Opepe and Obeche timber specimens exhibited more durable characteristics than their homogenous glulam when fabricated with PVA adhesive. The combined Opepe/Obeche (GLc OP/OB) glulam beam specimen was proposed into GL18c strength class according to EN 338 based on minimum constraints which it satisfies, reflecting a 41 % greater Modulus of Elasticity (MoE) in comparison with EN 338 experimental value. This study recommends the enhancement of the bending strength, density and modulus of elasticity of a typical non-durable solid Obeche timber beam by 38 %, 47 % and 35 % respectively with 40 % durable Opepe timber in a combined glulam form using PVA adhesive for engineering construction purposes.
Keywords: Opepe; Obeche; Timber; PVA Adhesive; Glulam; Beam; Strength